SELF-REGULATED LEARNING IMPLEMENTED BY THE STUDENTS OF ELEMENTARY SCHOOL IN BULELENG SUB-DISTRICT - Permatasai, N.P.I.; Mahayanti, N.W.S.; Nitiasih, P.K. (Universitas Pendidikan Ganesha, 2017)
This study highlights the implementation of each aspect of self-regulated learning in cyclical phase which was proposed by Zimmerman and Moylan (2009). With an aim to identify whether elementary school students in Buleleng Subdistrict implement self-regulated learning or not, this study used descriptive qualitatively research design to describe comprehensively the implementation of self-regulated learning in elementary school students. SDN 3 Banjar Jawa, SDN 4 Banyuasri, SD Laboratorium Undiksha, and SDN 4 Kampung Baru became the setting of this study because those schools have implemented curriculum 2013 which means that those schools have implicitly implemented self-regulated learning. There were 544 students from grade 1 until 6 which were chosen randomly as the subject of this study. The instruments used in this study were observation checklist, questionnaire which was consisted of 20 statements which had been distributed to subject of the study, and also interview guide which was used to interview several students from the subject of the study. The result of the study shows that most of elementary school students in Buleleng sub-district had implemented self-regulated learning.